1998
DOI: 10.1017/s1355838298980682
|View full text |Cite
|
Sign up to set email alerts
|

Probing of the spliceosome with site-specifically derivatized 5′ splice site RNA oligonucleotides

Abstract: We have developed a site-specific chemical modification technique to incorporate a photoreactive azidophenacyl (APA) group at designated internal positions along the RNA phosphodiester backbone. Using this technique, we have analyzed interactions of the 5' splice site (5'SS) RNA within the spliceosome. Several crosslinked products can be detected within complex B using the derivatized 5'SS RNAs, including U6 snRNA, hPrp8p, and 114-, 90-, 70-, 54-, and 27-kDa proteins. The 5'SS RNAs derivatized at intron positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The close contact between the 59SS and Prp8 extends beyond the GU dinucleotide at the 59 end of the intron+ Introduction of relatively small acetamide groups (;3 Å) attached through the ribose backbone at positions flanking the 59SS junction (from positions Ϫ2 to ϩ3) inhibits spliceosome formation, suggesting a steric hindrance in the interaction of Prp8 with the derivatized 59SS RNA (Sha et al+, 1998)+ Furthermore, photoreactive azidophenacyl groups attached to the 59 exon (positions Ϫ3, Ϫ4) form crosslinks with hPrp8 (Sha et al+, 1998), consistent with earlier reports of the 59 exon: Prp8 crosslinks (Wyatt et al+, 1992;Teigelkamp et al+, 1995a)+ In addition to Prp8, U2 and U6 snRNAs have also been implicated in interactions with the GU dinucleotide at the 59SS (Sontheimer & Steitz, 1993;Kim & Abelson, 1996;Luukkonen & Séraphin, 1998a, 1998b)+ Finally, the 59SS intron nucleotides positions ϩ4 to ϩ7 were shown to interact with U6 snRNA (Kandels-Lewis & Séraphin, 1993;Konforti et al+, 1993;Lesser & Guthrie, 1993;Sontheimer & Steitz, 1993) and a number of other spliceosomal proteins (Sha et al+, 1998)+ The multiplicity of factors that contact the 59SS region may explain why the GU:hPrp8 crosslinking is affected by both the exon and intron sequences flanking the 59SS junction (Fig+ 2)+ All these different interactions involving the 59SS contribute to the overall recognition of the substrate, its joining with the spliceosome, and its proper positioning at the active site of the complex+ The 59SS RNA:hPrp8 crosslink maps to a small segment in the C-terminal region of the protein To gain more insight into the interaction between the 59SS RNA and hPrp8, we identified the region of the protein involved in contacting the GU dinucleotide+ In the first approach, we carried out immunoprecipitation experiments using antibodies raised against two overlapping C-terminal regions of hPrp8 (70R and KO5 Abs; Fig+ 4)+ From a mixture of proteolytic fragments containing the crosslink, peptides as small as ;8-10 kDa could be immunoprecipitated with these antibodies, indicating that the site of crosslink is located within the C-terminal portion of hPrp8+ Formally, the crosslink should be located near the region recognized by both antibodies, that is, positions 1876-1902+ Because of some cross-reactivity of the KO5 Ab, we only considered the results obtained with the highly specific 70R Ab, effectively defining the crosslink site to a 50-60-kDa region at the C-terminus of hPrp8+ However, the results of the second mapping approach using a battery of endoproteolytic reagents to analyze the 59SS RNA:hPrp8 crosslink were consistent with the immunoprecipitation experiments+ The crosslink peptides obtained from digestions with a number of proteolytic reagents constituted a single product, indicating that the site of crosslinking is highly homogeneous within the hPrp8 sequence, and allowing for the high-resolution mapping of the crosslink+ By comparing the...…”
Section: Discussionmentioning
confidence: 99%
“…The close contact between the 59SS and Prp8 extends beyond the GU dinucleotide at the 59 end of the intron+ Introduction of relatively small acetamide groups (;3 Å) attached through the ribose backbone at positions flanking the 59SS junction (from positions Ϫ2 to ϩ3) inhibits spliceosome formation, suggesting a steric hindrance in the interaction of Prp8 with the derivatized 59SS RNA (Sha et al+, 1998)+ Furthermore, photoreactive azidophenacyl groups attached to the 59 exon (positions Ϫ3, Ϫ4) form crosslinks with hPrp8 (Sha et al+, 1998), consistent with earlier reports of the 59 exon: Prp8 crosslinks (Wyatt et al+, 1992;Teigelkamp et al+, 1995a)+ In addition to Prp8, U2 and U6 snRNAs have also been implicated in interactions with the GU dinucleotide at the 59SS (Sontheimer & Steitz, 1993;Kim & Abelson, 1996;Luukkonen & Séraphin, 1998a, 1998b)+ Finally, the 59SS intron nucleotides positions ϩ4 to ϩ7 were shown to interact with U6 snRNA (Kandels-Lewis & Séraphin, 1993;Konforti et al+, 1993;Lesser & Guthrie, 1993;Sontheimer & Steitz, 1993) and a number of other spliceosomal proteins (Sha et al+, 1998)+ The multiplicity of factors that contact the 59SS region may explain why the GU:hPrp8 crosslinking is affected by both the exon and intron sequences flanking the 59SS junction (Fig+ 2)+ All these different interactions involving the 59SS contribute to the overall recognition of the substrate, its joining with the spliceosome, and its proper positioning at the active site of the complex+ The 59SS RNA:hPrp8 crosslink maps to a small segment in the C-terminal region of the protein To gain more insight into the interaction between the 59SS RNA and hPrp8, we identified the region of the protein involved in contacting the GU dinucleotide+ In the first approach, we carried out immunoprecipitation experiments using antibodies raised against two overlapping C-terminal regions of hPrp8 (70R and KO5 Abs; Fig+ 4)+ From a mixture of proteolytic fragments containing the crosslink, peptides as small as ;8-10 kDa could be immunoprecipitated with these antibodies, indicating that the site of crosslink is located within the C-terminal portion of hPrp8+ Formally, the crosslink should be located near the region recognized by both antibodies, that is, positions 1876-1902+ Because of some cross-reactivity of the KO5 Ab, we only considered the results obtained with the highly specific 70R Ab, effectively defining the crosslink site to a 50-60-kDa region at the C-terminus of hPrp8+ However, the results of the second mapping approach using a battery of endoproteolytic reagents to analyze the 59SS RNA:hPrp8 crosslink were consistent with the immunoprecipitation experiments+ The crosslink peptides obtained from digestions with a number of proteolytic reagents constituted a single product, indicating that the site of crosslinking is highly homogeneous within the hPrp8 sequence, and allowing for the high-resolution mapping of the crosslink+ By comparing the...…”
Section: Discussionmentioning
confidence: 99%
“…To characterize spliceosomal proteins in proximity of the 59SS, we have used a previously described twostep chemical modification procedure (Sha et al+, 1998) to site-specifically couple a photoreactive BP group at internal positions within the RNA substrate+ The 11-nt 59SS RNA used in the first series of experiments (Fig+ 1A) contains a phosphorothioate residue at a specified position and carries in addition an adjacent 29-FIGURE 1. Under splicing conditions, the BP-derivatized 59SS RNA crosslinks to a set of protein factors within complex B+ A: The 11-nt 59SS RNA contains a single phosphorothioate residue at the specified position+ The position of modification refers to the phosphodiester bond at the 39 side of the indicated nucleotide+ The "/ " indicates the exon/intron junction+ B: Structure of a phosphorothioate RNA substrate used for derivatization reactions+ The middle nucleotide in the shown fragment contains the phosphorothioate modification+ C: Derivatization of the 32 P-thio-59SS (lane 1) with BPiodoacetamide couples the BP group to the sulfur in the 59SS RNA, resulting in a decreased mobility of the product in a 20% polyacrylamide/8 M urea gel (lane 2)+ D: Splicing reactions using the labeled 32 P-59SS RNA derivatized with BP at the indicated positions were incubated for 10 min at 30 8C, UV irradiated, and resolved in a 4% polyacrylamide native gel to monitor complex B formation+ The gel segments containing complex B from individual reactions were excised and resolved in a second dimension in a 15% SDS gel+ Positions of the 59SS:protein crosslinks and the molecular weight markers are indicated+ deoxy group (Fig+ 1B)+ Derivatization of this substrate with BP-iodoacetamide couples the BP group to sulfur in the 59SS RNA, resulting in a decreased electrophoretic mobility of the product (Fig+ 1C)+ Chemically synthesized 59-end 32 P-labeled, BP-derivatized 59SS RNA substrates, together with the 39SS RNA containing the branch site, polypyrimidine tract, and the 39 splice site, were used in bimolecular trans-splicing reactions in nuclear HeLa cell extracts (Konforti & Konarska, 1995)+ The reactions were irradiated with 302-nm UV light and the spliceosome complexes were resolved by nondenaturing gel electrophoresis+ As previously observed for the APA-derivatized substrates (Sha et al+, 1998), the bulky BP group positioned near the exon/intron junction (i+e+, from positions Ϫ3 to ϩ3) strongly interferes with complex B formation (Fig+ 1D, lanes 1-3, and data not shown)+ The inhibitory effects of bulky groups in this region of the 59SS RNA most likely reflect a steric hindrance with the hPrp8p:GU dinucleotide interaction (Reyes et al+, 1996;Sha et al+, 1998)+ This effect is not observed when BP is attached at more distal positions within the intron (positions ϩ4 to ϩ8), allowing for efficient complex B assembly (Fig+ 1D, lanes 4-8)+ To detect spliceosomal components that contact the 59SS through the BP group, UV-irradiated material present in complex B formed in individual reactions was first resolved in a nondenaturing gel and subsequently separated in an SDS-polyacrylamide gel (Fig+ 1D)+ Under these conditions, the 59SS RNA modified at intron positions ϩ7 or ϩ8 produces major crosslinks to p114 and p27 proteins (Fig+ 1D, lanes 7 and 8)+ In addition, several minor crosslink products, including hPrp8p, p150, p70, and p54, can be detected in these reactions+ The hPrp8p and p70 are crosslinked through thiol-nonspecific conjugation of BP occurring predominantly at adenosine residues in the 59 exon of the 59SS RNA (Konarska, 1999, and data not shown)+ The p150 can be detected only at early time point...…”
Section: Probing the Spliceosome With Site-specifically Derivatized 5mentioning
confidence: 99%
“…The RNA substrates were as described (Sha et al+, 1998;Konarska, 1999)+ The 59SS RNA used in Figure 1 contained the thiol and 29H groups at specified positions+ In all other experiments, a 59AAAAAG/GUAAGdT 32 P-dA-thio-dT39 RNA oligonucleotide was used+ Preparation of this substrate and its derivatization with benzophenone 4-iodoacetamide (Molecular Probes) was as described (Konarska, 1999)+ The extent of derivatization was monitored in a 20% polyacrylamide/ 8 M urea gel (Fig+ 1C)+ The 39SS RNA used in trans-splicing experiments contained a 83-nt intron and 45-nt exon transcribed from pBSAd13 plasmid (Konarska, 1989)+ For cis-splicing reactions, this RNA was ligated to the 32 P-labeled, BP-derivatized 59SS RNA described above to generate a full-length pre-mRNA substrate (Moore & Sharp, 1992;Konarska, 1999)+…”
Section: Rna Substratesmentioning
confidence: 99%
“…Interactions between the 59 splice site of the pre-mRNA and U1, U5, or U6 snRNAs that are supported by experiments+ U1 snRNA is believed to form a transient interaction with the 59 splice site prior to splicing and is replaced by U6 and U5 snRNAs that interact with the same sequences at the time splicing occurs+ Functional selection of 59 splice sites 167 are unknown (Liu et al+, 1998;Sha et al+, 1998;Ismaili et al+, 2001)+ A picture emerges where a given 59 splice site region is recognized through a complex network of interactions that changes during the course of splicing+ We have previously used an iterative functional selection approach to study the recognition of the branch point and 39 splice site (Lund et al+, 2000)+ Here we extend these studies by developing an in vitro strategy for iterative selection of functional 59 splice site sequences from a pool of pre-mRNAs containing randomized inserts+ We provide strong evidence for the hypothesis that factors other than the 59 end of the U1 snRNA determine the shape of the 59 splice site+ Moreover, based on splicing studies of individual pre-mRNAs with variable complementarity to the U1 snRNA, we conclude that stabilizing U1 snRNA binding to the 59 splice site in the natural range increases the competitive strength of a splice site, but concurrently inhibits the assembly of the full spliceosome+…”
Section: Introductionmentioning
confidence: 99%